2021
DOI: 10.3390/pathogens11010038
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Meningitis in Children: Reducing the Burden of Death and Disability

Abstract: Tuberculous meningitis disproportionately affects young children. As the most devastating form of tuberculosis, it is associated with unacceptably high rates of mortality and morbidity even if treated. Challenging to diagnose and treat, tuberculous meningitis commonly causes long-term neurodisability in those who do survive. There remains an urgent need for strengthened surveillance, improved rapid diagnostics technology, optimised anti-tuberculosis drug therapy, investigation of new host-directed therapy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 91 publications
0
29
0
Order By: Relevance
“…In a recent review by Huynh et al, 11 research gaps in pediatric TBM treatment were identified. These included (1) unclear optimal antituberculous drug dosing, regimen and duration (short versus 12 months) to effectively treat pediatric TBM, (2) lack of pediatric pharmacokinetic studies, (3) whether the dosage of isoniazid should be adjusted in fast compared to slow acetylators and (4) which of ethambutol (first-line antituberculous drug), ethionamide or the fluoroquinolones (second-line antituberculous drugs) is the best option as the fourth drug in a drug-susceptible TBM regimen in addition to rifampin, isoniazid and pyrazinamide.…”
Section: Research Gapsmentioning
confidence: 99%
“…In a recent review by Huynh et al, 11 research gaps in pediatric TBM treatment were identified. These included (1) unclear optimal antituberculous drug dosing, regimen and duration (short versus 12 months) to effectively treat pediatric TBM, (2) lack of pediatric pharmacokinetic studies, (3) whether the dosage of isoniazid should be adjusted in fast compared to slow acetylators and (4) which of ethambutol (first-line antituberculous drug), ethionamide or the fluoroquinolones (second-line antituberculous drugs) is the best option as the fourth drug in a drug-susceptible TBM regimen in addition to rifampin, isoniazid and pyrazinamide.…”
Section: Research Gapsmentioning
confidence: 99%
“…Central nervous system (CNS) tuberculosis mainly results from a primary MTB-infected pulmonary lesion that disseminates to the brain, spinal cord parenchyma, meninges, and surrounding tissues via the blood. CNS tuberculosis is relatively rare, accounting for 1-5% of all tuberculosis types, but it has a poor prognosis and fairly high fatality and disability rates (3)(4)(5)(6). Intraspinal tuberculosis is even rarer in clinical practice, mostly manifesting as tuberculous spinal meningitis and tuberculoma.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculous meningitis (TBM) disproportionately affects young children. 1 It is extra-pulmonary tuberculosis characterized by sub-acute inflammation of the meninges that covers the brain and spinal cord. 2 , 3 TBM is the most severe form of tuberculosis and is associated with high mortality and morbidity rates in children.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 TBM is the most severe form of tuberculosis and is associated with high mortality and morbidity rates in children. 1 , 4 Even if diagnosed and treated, nearly 20% of children die, and of those surviving more than half will suffer from a neurological disability. 5 In children, it develops shortly after primary pulmonary tuberculosis due to the hematogenous dissemination of Mycobacterium tuberculosis (MTB) bacilli.…”
Section: Introductionmentioning
confidence: 99%